Sophonisba, das funesto fine und die Nation: Auf- und Abschwung eines Opern- und Tragödienstoffs im langen 18. Jahrhundert - Winkler, Daniel (Artes, 2025)
Abstract: This article examines the rise and fall of the Sophonisba subject matter in 18th-century Italy, focussing on two genres, tragedy and opera seria. At the centre is the tension between dramatic poetics and politics, i.e. the focus is on the question of the form in which the material enjoyed particular popularity up to the threshold of modernity. In dramaturgical terms, the material oscillates between lieto and funesto fine. It is argued that the subject matter and poetics here, in the context of the ‘Roman’ Latin subject matter, are closely linked to a national appropriation and aesthetic valorisation that increasingly led to the development of a dramaturgy of amore e patria. This reveals, on the one hand, a quasi-serial popularity of the material in the extremely hybrid opera seria and thus in theatre practice, which is dominant in the course of the 18th century, and, on the other hand, the classicistically renewed tragedy aesthetic as a counter-model of a ‘sublime’ national poetics, which is to be located in the run-up to risorgimental (theatre) literature. Following on from remarks on the history of drama and opera, two works will be discussed in more detail here with regard to the drama aesthetics of the funesto fine: Mattia Verazi’s libretto for the composer Tommaso Traetta (1762) and Vittorio Alfieri’s tragedy Sofonisba (1784/88). The aim is to make it clear that opera and tragedy, despite all the differences in poetics and theatre practice, are closely interwoven, particularly with regard to popular Italian material, including the dramaturgy of political and amorous liberty.
Gesehen am 07.08.2025
Publikationsdatum: 06. Mai 2025 (Online)